Blending critical thinking skills with the teaching of subject matter: Case of a geography lesson in a Malawi school - Mgomezulu, Victor Y.; Shawa, Lester B.; Wamba, Nathalis G. (AJOL, 2014)
Critical thinking skills are essential in education. Unfortunately, education policymakers and curriculum developers in Malawi have not given a concerted effort to promoting critical thinking skills in schools. OSISA has indicated that there is no clear evidence in the Malawi primary and secondary school curricula that promoting critical thinking is considered important. In this paper, we examine the definitions of critical thinking, creative thinking, reflective thinking and we are of the view that there is a level of overlap amongst them. We also look at how the behaviours of egocentrism and sociocentrism can undermine critical thinking. The study draws on Piaget and Vygotsky’s theory of (social) constructivism to advance approaches and practices that teachers can employ to promote critical thinking in learners. We develop a lesson plan that incorporates critical thinking skills and show how teachers can correct egocentric and sociocentric tendencies that might impede critical thinking in learners. We claim that students equipped with critical thinking skills can contribute intellectually, socially, culturally and economically to society.
Keywords: social constructivism; lesson plan; egocentric; sociocentric